Resignifying the Unexpected: Career Shocks and its Impacts on the Trajectories of Executive Women - Anna Paula Visentini; Camila Vieira Müller; Angela Beatriz Scheffer (BBR: Brazilian Business Review)
Career shocks are extraordinary, unforeseen events that lead to individual reflections on personal and professional directions. The article aims to identify career shocks as drawn from narratives of 20 women, in corporate careers, who carried out transitions in their trajectories, and to understand how these shocks impact on the sustainability of careers in time. Focusing on female careers beyond motherhood, the interviewees had no children when they made the transition. The analysis revealed four shocks: Awareness on the finitude of life and resignification of trajectories, Focus on the balance between Work-Life after Harm to Physical and Mental Health, Transformative Experiences and Search for Sense, and the Covid-19 Pandemic’s impact on the working modes. These shocks boosted movements toward more sustainable trajectories, demonstrating that the subjective character of careers allows the positive valuation of experiences commonly considered negative. Career shocks, in addition to revealing opportunities, signaled restrictions in women’s career contexts.